Art and the ‘Second Darkness’ - Catherine Lanone (Cahiers Victoriens et Edouardiens)
This paper examines E. M. Forster’s crucial yet peripheral relationship with the Bloomsbury Group. A diffident, keen observer, Forster stressed the way in which Bloomsbury shattered Victorian conventions. He describes the Bloomsbury legacy in terms of aesthetic change, such as Virginia Woolf’s rhythmical sensuous prose or Lytton Strachey’s ironic, revolutionary biographies. But he also helps us to define this legacy in more political terms, as the ethos of art and personal relationships was confronted with the rise of fascism. Today Bloomsbury is perceived in contradictory, controversial ways; yet its legacy discreetly survived the war, under new guises such as the B.B.C. Third programme.